The activity kit for babies and toddlers at risk : how to use everyday routines to build social and communication skills - Fein, Deborah (New York : The Guilford Press, 2016)
Suspecting that your baby or toddler may have autism spectrum disorder or another developmental delay can be scary and overwhelming. But there is a lot you can do to help, even while waiting for an evaluation or early intervention. In this guide, leading experts present more than 100 games and activities designed to support development in children from birth to age 3. Your child's daily routines are transformed into learning opportunities that promote crucial abilities, like how to imitate others or use simple hand gestures to convey wants and needs. As a parent, you are the most important person in your child's life. Now you can be the best teacher, too.
Introduction: Is this book for you? -- Helping babies and toddlers learn and develop. What is a developmental delay and how can games in routine activities help? -- Keystones: Attachment and behavioral teaching -- 12 rules to play by -- Language, eye contact, and imagination: Important targets of learning -- Games and activities for toddlers at risk. Waking up and going to sleep -- Dressing, undressing, and diaper changing -- Mealtime -- Bathtime -- Chores -- Errands -- Indoor play -- Outdoor play -- Games and activities for babies at risk. 0-3 months -- 3-6 months -- 6-9 months -- 9-12 months -- More tips and tools. Specific words, phrases, gestures, and signs to work on -- Preventing problem behavior.
Includes bibliographical references and index.
Keywords: Developmentally disabled children -- Behavior modification; Parents of developmentally disabled children; Developmental disabilities -- Treatment